Placebo Effects in Sport and Exercise: A Meta-Analysis - Bérdi, Márk; Köteles, Ferenc; Szabó, Attila; Bárdos, György (European Journal of Mental Health, 2011)
The empirical foundation of the ‘placebo effect’ is presented briefly, which is followed by the meta-analysis of the relatively few published reports that have investigated placebo effects in sports performance. Based on the analysis of the fourteen studies included in the meta-analysis, an overall medium effect size (0.4, 95% CI ranged from 0.24 to 0.56) was found. Homogeneity of effect sizes (χ2 (13, N = 196) = 9.35, p = 0.75) and the feasibility of possible explanation models were also tested. In various sports (e.g. cycling, running, weightlifting) the investigation of the placebo effect on various physiological or performance measures (e.g. muscle power, heart rate, running speed) and psychological attributes (e.g. perceived exertion, post-experiment interviews) yielded significant results. Indeed, the common finding of the reviewed studies was that from the point of view of the athletes there is substantial performance enhancement as a result of different forms of placebos. However, the interpretation of some of the results may be limited by methodological shortcomings. Based on the reviewed articles and further questions emerging from them, methodological recommendations as well as possible research ideas are suggested for further inquiries in the area.